EFEKTIFITAS PENGOLAHAN UBI JALAR TERHADAP PENINGKATAN EKONOMI MASYARAKAT DITINJAU DARI EKONOMI ISLAM: (Studi Kasus di Home Industri Asri Food Wonosalam Jombang ) - Feradini (Irtifaq, 2022)
This research intends to analyze the effectiveness of sweet potato processing on improving the community's economy in terms of Islamic economics. This study used primary data sources derived from field data and secondary data obtained from appropriate literature reviews. After the data collection process will be done analysis that uses inductive and descriptive methods. Data analysis is used to find out how Home Industry's effectiveness in improving the community's economy. This research uses case research and phenomenological approaches. Keywords: Effectiveness, Home Industry, Community Economic Improvement